Representasi dan Komodifikasi Kepiluan dalam Film Dancing In The Rain - Ilma Saakinah Tamsil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The film tells stories and theme about the suffering of others as a humanist always aim to arouse the emotions and feelings of the audiences. This Film get a lot of positive responses from various parties, especially films that emphasize the sorrow. The purpose of this paper is to analyze the narrative structure of the film Dancing In The Rain as a representation and commodification of depression for the audience. The author uses a qualitative descriptive study in which the representation and commodification of heartache in Dancing In The Rain movie is analyzed through the analysis of narrative structure according to Tzvetan Todorov, the presentation of moral values in the film, and the relation with the culture industry as a medium for image formation. How the sadness and heartache of autistic sufferers is commodified as a product that entertains and motivates the audiences. The conclusion, the reality in the film will be a learning through representation and the commodification of heartache give a description of the conditions, experiences and problems faced by the main character (autistic sufferers) struggling to faced life.